PEMBINAAN RESIDIVIS UNTUK MENCEGAH PENGULANGAN TINDAK PIDANA DI RUMAH TAHANAN KELAS II A SAMARINDA - Tiar Tiar (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
Crime is an integral part of human life in the world. All human activity whether political, social and economic, can be a crime movement. Referred to as a criminal offender. Understanding the value derived from nature, then he has a very relative sense, ie depending on the man who pass judgment. So what are called crimes by someone not necessarily recognized by others as a crime anyway. If for example all classes can receive something that is a crime but the severity of the act was still causing disagreements. So that the existence of evil does not need to be sad, but it should always be sought effort how to handle it. Trying to suppress the quality and quantity as low as possible, the maximum according to the circumstances and conditions.